Petrogenesis and tectonic setting of ore-related porphyry in the Duobaoshan Cu deposit within the eastern Central Asian Orogenic Belt, Heilongjiang Province, NE China. (1st October 2018) - Zhao, Chao; Qin, Kezhang; Song, Guoxue; Li, Guangming; Li, Zhenzhen; Pang, Xuyong; Wang, Le
Graphical abstract: Highlights: The ore-related porphyry shows a mantle source with depleted Sr, Nd, Hf, and O isotopic features. The Duobaoshan granitoids are derived from melting of a thickened juvenile mafic lower crust. The Duobaoshan deposit was formed in a subduction-related arc setting. Abstract: The Duobaoshan porphyry Cu deposit (2.37 Mt Cu @ 0.47%; 73.4 tons Au @ 0.144 g/t and 80, 000 tons Mo @ 0.016%) is located in the eastern part of the Central Asian Orogenic Belt (CAOB). Mineralization mainly occurs in the granodiorite and Ordovician volcanic rocks, and SIMS zircon U-Pb dating indicates that the ore-forming granodiorite porphyry emplaced at around 477 Ma. In addition, whole-rock major and trace element compositions show that the granodiorite porphyry belongs to a high-K to medium-K calc-alkaline series and has an affinity of adakitic rocks with high Sr, and low Y and Yb. Granodiorite porphyry samples are enriched in large ion lithophile elements (LILE) and light rare earth elements (LREE), and are depleted in high field strength elements (HFSE) and heavy rare earth elements (HREE). Their geochemical natures show a high Ni content (average 45.5 ppm) and Mg # value (average 46). The granodiorite porphyry shows very low initial 87 Sr/ 86 Sr ratios (from 0.70279 to 0.70414) and low δ 18 O (mean = +5.38‰), very high ɛNd (t) values (mean = +4.7) and ɛHf (t) values (mean = +12.11), and very young two-stage Hf and Nd model ages (average 765 Ma and 827 Ma, respectively). Given that the ore-related intrusions are coeval with the high-Mg diorites and andesites in the region, it is proposed that both the ore-related granodiorite porphyry and granodiorite were derived from melting of a thickened juvenile mafic lower crust, which was induced by underplating of melts from a depleted mantle wedge above a subduction zone. A certain proportion of slab melts may also have been involved in the magmas that produced ore-related intrusions.